Implantable Cardioverter Defibrillator in Sport Participation - Mascia, G.; Di Biase, L.; Galanti, G.; Natale, A.; Padeletti, L. (International Journal of Sports Medicine, 2014)
Although athletic participation lowers cardiovascular risk and improves quality of life, it may represent a hazard in high-risk group athletes such as those with cardiac abnormalities receiving an implantable cardioverter defibrillator (ICD). ICD sports participants are exposed to the potential risk of inappropriate shocks due to sinus tachycardia and other supraventricular arrhythmias during exertion as well as device injury. The safety of athletic participation of ICD-patients is not completely defined and ICD efficacy in interrupting malignant arrhythmias during intense exercise is partly unknown. This explains difficulties in current recommendations made by physicians, given the associated potentially ischemic, autonomic and metabolic conditions. The scope of this review is to underline specific considerations including potential risks and recommendations for athletic participation in this patient-group.
Keywords: athletes; arrhythmias; sudden cardiac death; defibrillators